The Impact of Strategic Awareness on Enhancing Organizational Immunity System: An Applied Study on Jordanian Food Manufacturing Companies - Al-Badayneh, Ghazy (International Review of Management and Marketing, 2021)
This study aimed at identifying the impact of strategic awareness on enhancing the regulatory immune system, an applied study on Jordanian food processing companies. For the purpose of achieving the objectives of the study, the researcher used the descriptive and analytical approach, the researcher developed a questionnaire to collect data related to the study variables. (160) questionnaires were distributed on an intentional sample consisting of (13) food processing companies. The questionnaire targeted managers and workers in the directorates of production, quality, and planning in the searched companies. The number of retrieved questionnaires reached (150) questionnaires are suitable for analysis, the researcher used multiple regression analysis through the Statistical Package in Social Sciences (SPSSv.19) to test the study hypotheses, and the study reached results, the most important results are: That the study sample individuals 'perceptions of the strategic awareness in the researched companies were of a high level, and the study sample's perceptions of the organizational immune system in the researched companies were of a high level. The study recommends the need to strengthen the supporting culture to the concept of organizational immunity between senior management and employees, the need to work with strategic awareness because of its great impact on strengthening the regulatory immune system and its ability to convert knowledge into applied practices, in addition to following an interest in strategic awareness in its various dimensions, development and enhancing it among Jordanian food processing companies. Keywords: strategic awareness, regulatory immune system, Jordanian food processing companies. JEL Classifications: L1, L66 DOI: https://doi.org/10.32479/irmm.11239